2022
DOI: 10.3390/children9020271
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness for Life-Threatening Situations in a Pediatric Tertiary-Care University Children’s Hospital: A Survey

Abstract: Pediatric nurses and physicians are rarely exposed to life-threatening events. Understanding the needs of clinicians is key for designing continuing training programs. A survey exploring preparedness to manage life-threatening events as well as training needs was mailed to all clinically active nurses and physicians at a tertiary-level referral children’s hospital. Overall, 469 participants out of 871 answered the questionnaire (54% response rate). Respondents felt well or very well (nurses 93%, physicians 74%… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This may be related to the characteristics of the different majors. Compared to doctors, nurses usually start to contact patients at the early stage of their training [55] and have more extensive and intimate interactions with patients during the whole nursing process [56,57]. Research indicated that possessing a healthy shape may enhance individuals' body image and physical attractiveness [53].…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the characteristics of the different majors. Compared to doctors, nurses usually start to contact patients at the early stage of their training [55] and have more extensive and intimate interactions with patients during the whole nursing process [56,57]. Research indicated that possessing a healthy shape may enhance individuals' body image and physical attractiveness [53].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed,barriersbetweentheoreticalknowledgeandrealpractice still need to be tackled. 6,8,11 Could simulation scenarios, communication training or continuative support be potential ways forward? 4.…”
Section: E D I T O R I a L Some Like It Hotmentioning
confidence: 99%
“…Will this body of knowledge translate in better practice? Indeed, barriers between theoretical knowledge and real practice still need to be tackled 6,8,11 . Could simulation scenarios, communication training or continuative support be potential ways forward? Fourth, could a similar efficacy be achieved also among paediatric residents, nurses, and parents? Fifth, regional or cultural differences might be expected 12,13 : how should the teaching sessions be tailored to different geographical backgrounds and attitudes?…”
mentioning
confidence: 99%
“…However, most HCPs are unfamiliar with how to perform prone position cardiopulmonary resuscitation (PPCPR) (To l et al, 2014). Ulmer et al (2022) identi ed a gap between HCPs' preparedness to respond to life-threatening situations in terms of training and applying those acquired skills to the bedside con dently (Ulmer et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HCPs perceive that they are well prepared to perform CPR in terms of knowledge and skills. However, Ulmer et al (2022) found that HCPs' response to life-threatening situations is still of concern (Ulmer et al, 2022).…”
Section: Introductionmentioning
confidence: 99%